PENGEMBANGAN MODEL PEMBELAJARAN TEMATIK SENI DAN BUDAYA MENGGUNAKAN VIDEO TEATERIKALISASI COWONGAN DI SEKOLAH DASAR - Irawati, Anastasia Dwi Wiwik; Kuntoro, Kuntoro; Jazuli, Akhmad (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This study aims to develop a thematic learning model of art and culture using video theatericalization of “Cowongan” for students in elementary schools. This research is a research development that aims to improve the ability to verbalize “Kidung Kasengsaraan Mangsa Ketiga” with the Banyumas dialect. The research design uses R and D Data collection techniques in research gather information, product design, product validation, product testing, design revision, trial use, product revision, mass production, and dissemination. These data sources are interviews, observations, taking questionnaires, and tests. The sampling technique uses cluster sampling as the population of SDN 4 Sokanegara students. The results of research in verbalizing the geguritan include laval, intonation, placement of pauses, and expressions. The observations of researchers obtained data that the average posttest results that the experimental class reached 90% of the expected score, while the average control class reached 75.75% of the expected score. The results of the effectiveness test in the research prove that the class that uses the product is better than the one that does not use the product so that the ability to speak up using the Banyumas dialect is more effective.